Estimating the wage premia of refugee immigrants: Lessons from Sweden - Christopher F. Baum; Hans Lööf; Andreas Stephan; Klaus F. Zimmermann (Global Labor Organization (GLO), 2024)
This paper examines the wage earnings of fully-employed previous refugee immigrants in Sweden. Using administrative employer-employee data from 1990 onwards, about 100,000 refugee immigrants who arrived between 1980 and 1996 and were granted asylum, are compared to a matched sample of native-born workers. Employing recentered influence function (RIF) quantile regressions to wage earnings for the period 2011-2015, the occupational-task-based Oaxaca-Blinder decomposition approach shows that refugees perform better than natives at the median wage, controlling for individual and firm characteristics. This overperformance is due to female refugee immigrants, who have-relative to their endowment-higher wages than comparable native-born female peers up to the 8th decile of the wage distribution. Given their endowments, refugee immigrant females perform better than native females across all occupational tasks studied, including non-routine cognitive tasks. A remarkable similarity exists in the relative wage distributions among various refugee groups, suggesting that cultural differences and the length of time spent in the host country do not significantly affect their labor market performance.
Keywords: C23; F22; J24; J6; O15; 330; refugees; wage earnings gap; occupational sorting; employer-employee data; correlated random effects model; Blinder-Oaxaca decomposition